Fairness: from the guts to the brain – a critical examination by Atlantic fellows of the Global Brain Health Institute - Avelino-Silva, Thiago Junqueira; Trujillo, Natalia; Udeh-Momoh, Chinedu (Frontiers in Psychology, 2023)
In January 2023, the Global Brain Health Institute (GBHI) at UCSF hosted an online salon to discuss the relationship between fairness and brain health equity. We aimed to address two primary questions: first, how is fairness perceived by the public, and how does it manifest in societal constructs like equity and justice? Second, what are the neurobiological foundations of fairness, and how do they impact brain health? Drawing from interdisciplinary fields such as philosophy, psychology, and neuroscience, the salon served as a platform for participants to share diverse perspectives on fairness. Fairness is a multifaceted concept encompassing equity, justice, empathy, opportunity, non-discrimination, and the Golden Rule, but by delving into its evolutionary origins, we can verify its deep-rooted presence in both human and animal behaviors. Real-world experiments, such as Frans de Waal’s capuchin monkey study, have proven enlightening, elucidating many mechanisms that have shaped our neurobiological responses to fairness. Contemporary cognitive neuroscience research further emphasizes the role of neuroanatomical areas and neurotransmitters in encoding fairness-related processes. We also discussed the critical interconnection between fairness and healthcare equity, particularly its implications for brain health. These values are instrumental in promoting social justice and improving health outcomes. In our polarized social landscape, there are rising concerns about a potential decrease in fairness and prosocial behaviors due to isolated social bubbles. We stress the urgency for interventions that enhance perspective-taking, reasoning, and empathy. Overall, fairness is vital to fostering an equitable society and its subsequent influence on brain health outcomes.